Achieving and sustaining secured business operations : an executive's guide to planning and management - Ajmani, Neelesh; Kumar, Dinesh (Apress, 2017)
Proactively plan and manage innovation in your business while keeping operations safe and secure. This book provides a framework and practices to help you safeguard customer information, prevent unauthorized access, and protect your brand and assets. Securing company operations is a board-level discussion. Across all industries, companies are pouring millions of dollars into taming cybercrime and other related security crime. Achieving and Sustaining Secured Business Operations presents a holistic approach looking top down, bottom up, and sideways. The end goal is to achieve and sustain a safe environment to conduct secured business operations while continuously innovating for competitive advantage. What You'll Learn: Discover why security, specifically secured business operations, needs to be part of business planning and oversight by design and not left to technologists to make the business case Determine what you can do in your role and in your organization to drive and implement integration and improvements in planning and managing secured business operations in conjunction with other business planning and management activities Choose ways in which progress toward achieving and sustaining secured business operations can be measured Understand best practices for organizing, planning, architecting, governing, monitoring, and managing secured business operations Create a framework, including methods and tools for operationalizing assessment, planning, and ongoing management of secured business operations Use cases and potential case studies for various industries and business models.